Identification of a New Infectious Pancreatic Necrosis Virus (IPNV) Variant in Atlantic Salmon (Salmo salar L.) that can Cause High Mortality Even in Genetically Resistant Fish - Hillestad, Borghild; Johannessen, Stein; Melingen, Geir Olav; Moghadam, Hooman K. (Frontiers in Genetics, 2021)
Infectious pancreatic necrosis (IPN) is an important viral disease of salmonids that can affect fish during various life cycles. In Atlantic salmon, selecting for genetically resistant fish against IPN has been one of the most highly praised success stories in the history of fish breeding. During the late 2000s, the findings that resistance against this disease has a significant genetic component, which is mainly controlled by variations in a single gene, have helped to reduce the IPN outbreaks to a great extent. In this paper, we present the identification of a new variant of the IPN virus from a field outbreak in Western Norway that had caused mortality, even in genetically resistant salmon. We recovered and assembled the full-length genome of this virus, following the deep-sequencing of the head-kidney transcriptome. The comparative sequence analysis revealed that for the critical amino acid motifs, previously found to be associated with the degree of virulence, the newly identified variant is similar to the virus’s avirulent form. However, we detected a set of deduced amino acid residues, particularly in the hypervariable domain of the VP2, that collectively are unique to this variant compared to all other reference sequences assessed in this study. We suggest that these mutations have likely equipped the virus with the capacity to escape the host defence mechanism more efficiently, even in the genetically deemed IPN resistant fish.